Education and federalism: The vicissitudes of financing and governance in the National Education Plan - Oliveira, Weder de (Education Policy Analysis Archives, 2021)
This research discusses two dimensions of the Brazilian National Education Plan. The first covers the institution and functioning of the instances of negotiation and federative coordination, the regulation of the National Education System (SNE), and the role of the Ministry of Education (MEC) in monitoring, evaluating, and articulating the plan development. The second refers to Goal 20: the expansion of public investment in education to 10% of the GDP by the end of the decade. Our research was based on evaluations by the Federal Court of Accounts, INEP, IPEA, and the House of Representatives seeking to learn whether these dimensions have been developed adequately. The results indicate that Goal 20 is unattainable, the performance of the intergovernmental coordination instances is still incipient, and MEC, the central actor in planning, articulating, and promoting educational policies, suffers from relevant planning and management deficiencies. Such weakness of these dimensions reduce the chances of successfully implementing the PNE. From the point of view of fiscal federalism, intergovernmental relations, and governance of public policies in education, our study also highlights that the Federal Constitution assigned to a long-term national plan functions that are extremely difficult to accommodate in a single legislative instrument, resulting in inevitable omissions and problems that worsen the low expectation of satisfactory implementation, which, however, does not mean that advances in educational policies have not occurred or are not underway, regardless of the deficiencies of this federal planning strategy.